RANCANGAN AWAL SISTEM KOMUNIKASI SATELIT IMAGE PROCESSING LAPAN-TUBSAT - Suwarjo, Minto (Indonesian Journal of Aerospace, 2003)
The LAPAN-TUBSAT is a joint reseaverd between LAPAN and TECHNICAL UNIVERSITY OF BERLIN for image processing application. The satellite will be built in with half-duplex transmission system, with uplink frequency is uHF-band 435.075 Mhz in minimum data rate 1200 pbs, while the downlink frequency is S-band 2.2 GHz use data rate 38400 bps. The uplink frequency will functioned for command and donwlink frequencies for telemetry data and image data. The main communication payload consists of transmitter and antenna s-band, tranceiver and antenna UHF-band, two cameras with resolution 50 mm and 1000 mm with PAL standard, data and video multiplexes, on borad data handling and power control unit. The ground station consists of TT and C operates in UHF-band and ground receiver processing operates in S-band frequency. The minimum image signal quality received is 45 dB for BER 10.